2015
DOI: 10.1002/nbm.3281
|View full text |Cite
|
Sign up to set email alerts
|

4D MRI of polycystic kidneys from rapamycin‐treated Glis3‐deficient mice

Abstract: Polycystic kidney disease (PKD) is a life-threatening disease that leads to a grotesque enlargement of the kidney and significant lose of function. Several imaging studies with MRI have demonstrated that cyst size in polycystic kidneys can determine disease severity and progression. In the present study, we found that while kidney volume and cyst volume decreased with drug treatment, renal function did not improve with treatment. Here, we applied dynamic contrast-enhanced MRI to study PKD in a Glis3-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There has been increased interest recently in the development of imaging tools to probe microstructure with MRI 11 , 12 . Recently, a cationized form of ferritin (the predominant mammalian iron-storage protein) has been developed as a contrast agent for MRI to measure kidney glomerular morphology 10 , 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been increased interest recently in the development of imaging tools to probe microstructure with MRI 11 , 12 . Recently, a cationized form of ferritin (the predominant mammalian iron-storage protein) has been developed as a contrast agent for MRI to measure kidney glomerular morphology 10 , 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, ultrasound can detect renovascular expression of adhesion molecules (3), whereas computed tomography is a powerful tool to quantitate renal hemodynamics (4). Initially used to detect scar formation in the kidney, magnetic resonance imaging (MRI) is now employed to interrogate a range of functional and structural parameters in the kidney during preclinical studies (7,19,21).…”
Section: Introductionmentioning
confidence: 99%
“…This architecture has been shown to generalize even from a limited amount of annotated data [25], and as such is well suited for medical imaging, where datasets as large as the ones commonly used for CNNs are rare. Valverde et al [26] recently demonstrated the effectiveness of U-Net-like architectures in preclinical research, designing the first DNN for the segmentation of ischemic lesions in rodents and achieving segmentation accuracy comparable or better to inter-rater agreement in manual segmentation.…”
mentioning
confidence: 99%